Sieniawa Lignite Mine - extraordinary history, geology and mining achievements during the last decade - Bik, Andrzej; Jarosz, Jerzy; Widera, Marek; Worobiec, Elżbieta (Geologos, 2026)
In the Lubusz region (western Poland), lignite was already mined in the first half of the 19th century. German exploitation of the lignite proceeded on an industrial scale and continued until the end of World War II. After the war, Poland took up excavations in this area, but exclusively at the Sieniawa Lignite Mine (SLM). This mine, the smallest in Poland, was state-owned for over half a century; since 2002 it has been a private company. Annual lignite production at SLM rarely exceeded 0.1–0.2 million tonnes (Mt), although, in recent years, it has increased significantly, reaching a record level of over 1 Mt. These mining achievements are particularly impressive within the context of the highly complex geological structure of the study area. For over 150 years, SLM has been exploiting one of the most glaciotectonically disturbed lignite seams in the world, first underground and later in opencast. This lignite belongs to the 2nd Lusatian group of seams, is of late Early–early Middle Miocene age, having formed under the conditions of the Miocene Climatic Optimum. The wetland vegetation (swamp forests and shrub bogs) in the warm, near-subtropical climate produced large amounts of peat, which ultimately led to lignite formation. Detritic lignite dominates (followed by xylodetritic lignite) and is characteristically weathered in its upper part, containing numerous traces of wildfires. Finally, despite the energy transformation, SLM has a chance to continue operating for at least several more decades, this being the longest amongst all Polish lignite mines.